Eosinophilic esophagitis: an interdisciplinary clinical problem - Wojas, Oksana; Żalikowska-Gardocka, Marta; Krzych-Fałta, Edyta; Samoliński, Bolesław; Przybyłkowski, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Eosinophilic esophagitis is a newly described entity of increasing incidence. Previously thought to be a variation of gastroesophageal reflux disease, now it becomes well known among gastroenterologists, allergologists, paediatricians and pathologists. Aetiology of the disease is strongly correlated with atopic and allergic disorders but exact pathogenesis and cellular mechanisms of inflammatory process in the esophagus are still unknown. Diagnostic criteria have been described but diagnostic tools are still in the research and improvement phase. Clinical manifestation varies considerably between age groups, which causes a delay in the course of diagnosis due to improperly recognized symptoms. Since eosinophilic esophagitis is a chronic disease without a tendency to be self-limiting, delayed diagnosis may lead to complications associated with oesophageal tissue remodelling. Some forms of treatment are approved and of great therapeutical value, nevertheless clinical trials of new medications provide new possibilities. Therefore, many questions regarding eosinophilic esophagitis arise and are still unanswered.